2015
DOI: 10.3389/fmicb.2015.00979
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and high-throughput sequencing analysis—modern approach for the assessment of biodeterioration of materials from historic buildings

Abstract: Preservation of cultural heritage is of paramount importance worldwide. Microbial colonization of construction materials, such as wood, brick, mortar, and stone in historic buildings can lead to severe deterioration. The aim of the present study was to give modern insight into the phylogenetic diversity and activated metabolic pathways of microbial communities colonized historic objects located in the former Auschwitz II–Birkenau concentration and extermination camp in Oświecim, Poland. For this purpose we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 62 publications
1
47
0
1
Order By: Relevance
“…The metabolism of P. aeruginosa inhabiting fabrics can cause changes in the content of elements, as has previously been reported for microbial communities growing on historical materials. Gutarowska et al [26] observed the activation of numerous metabolic pathways, including those regulating the production of primary and secondary metabolites, including metabolites associated with the deterioration of organic compounds. growing on historical materials.…”
Section: Degradation Of Archeological Textiles By P Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of P. aeruginosa inhabiting fabrics can cause changes in the content of elements, as has previously been reported for microbial communities growing on historical materials. Gutarowska et al [26] observed the activation of numerous metabolic pathways, including those regulating the production of primary and secondary metabolites, including metabolites associated with the deterioration of organic compounds. growing on historical materials.…”
Section: Degradation Of Archeological Textiles By P Aeruginosamentioning
confidence: 99%
“…growing on historical materials. Gutarowska et al [26] observed the activation of numerous metabolic pathways, including those regulating the production of primary and secondary metabolites, including metabolites associated with the deterioration of organic compounds. Analysis of the infrared absorption spectra of the archeological fibers before and after biofilm formation in comparison to contemporary alpaca fibers revealed significant changes in the molecular structure of the keratin (Figure 2).…”
Section: Degradation Of Archeological Textiles By P Aeruginosamentioning
confidence: 99%
“…Actinobacteria have been frequently found as a dominant group in subterranean micro-niches, including cultural relics in caves and wall paintings in catacombs [13][14][15][16][17]. Previous work demonstrated that some Actinobacteria are potentially harmful to the preservation of cultural relics [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Some sophisticated studies add little to earlier findings using traditional methods 11 . There are also several technological artefacts and innate biological traits that bias relative quantification of abundance 19 , although a combination of electron microscopy with metabolomic and genomic techniques allowed some linkage of phylogenetic data with metabolic profiles 21 . However, such studies describe functional potential, and it is difficult to definitively link phylogeny and function 20,22 .…”
Section: Sequencing-based Surveys Of the Built Environmentmentioning
confidence: 99%